The Role of Product Quality, Customer Reviews, Ratings, and E-WOM in Shaping Purchase Decisions for Skintific Products on Shopee - Putri, Dea Yosiana; Astuti, Herni Justiana; Handayani, Erna; Haryanto, Totok (Asian Journal of Management Analytics, 2025)
This study analyzes the impact of product quality, online customer reviews, customer ratings, and e-WOM on purchasing decisions for Skintific products on Shopee. Using a quantitative approach, this study involved 100 students from three of the largest universities in Purwokerto who had purchased Skintific products. The sample was selected through purposive sampling. The results showed that product quality and online customer reviews significantly influenced purchasing decisions, surpassing the impact of customer ratings and e-WOM. E-WOM was found to have no significant impact, providing a new perspective on digital marketing strategies on Shopee. This study contributes to a deeper understanding of consumer behavior in e-commerce, by emphasizing the important role of product quality and reviews in shaping purchasing decisions.